Peran Kesadaran Warga dan Sistem Pengelolaan Karang Taruna dalam Penarikan Iuran Warga RT 15 Geluran Taman Sidoarjo - Ningsih, Ella Amalia (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Community dues are a form of public participation in supporting social activities and neighborhood development. However, low participation in paying dues remains a common issue in many communities. This study aims to analyze the role of community awareness and the management system of youth organizations in improving the effectiveness of dues collection in Neighborhood 15, Geluran, Sidoarjo. The method used is Asset-Based Community Development (ABCD), with data collected through observation, interviews, and focus group discussions. The results show that increased community awareness, supported by continuous socialization, has positively influenced residents’ perceptions, transforming dues from being seen as a burden into a shared responsibility. In addition, improvements in management systems, including transparent financial recording and regular reporting, have strengthened public trust. The findings also indicate a strong relationship between awareness and management systems, where transparency enhances trust and encourages higher participation. Furthermore, the ABCD approach successfully utilizes local assets such as youth involvement and social solidarity, leading to strengthened community engagement and the emergence of local leadership. Despite these improvements, some residents still show inconsistent participation, indicating the need for continuous efforts to sustain the program. This study highlights the importance of integrating awareness-building and transparent management to achieve sustainable community participation.